Analysis of ERP Implementation in Perum BULOG with Extended TAM 3 Approach - Muhammad Ainul Fahmi; Udisubakti Ciptomulyono; Jani Rahardjo (Institut Teknologi Sepuluh Nopember, 2020)
Several previous studies explained that the implementation of an integrated information system needed to be realized at Perum BULOG because the old system has not been integrated. This was also realized by the management of Perum BULOG by carrying out one of its long-term plans, namely carrying out the implementation of ERP system in 2020. On the other hand, ERP is a complex system because ERP systems often adds more difficulties to the implementation process. Therefore, it is necessary to conduct research on the analysis of ERP implementation at Perum BULOG to see how ERP users will accept this technology using the extended TAM 3 approach. Outer Model and Inner Model are used to test and analyze data from research instruments using the SMART PLS 3.0. Based on the research findings, it can be seen from 12 research hypotheses, 9 research hypotheses were accepted and 3 were rejected. It is known that perceived usefulness is found only factor in system- technology ERP and perceived ease of use which have a positive and significant correlation. Meanwhile, the perceived ease of use factor was found only the organization process characteristic and system-technology ERP factor that had a positive and significant correlation. Furthermore, the attitude factor of ERP user is influenced by the perceived usefulness and perceived ease of use. Where the ERP user attitude factor is able to encourage behavioral intention and have implication for use and user satisfaction.